The Problem of Secondary Effects. Issue 2 (June 2016) - Engelhardt, Jeff
ABSTRACT: This paper argues that two principles held by many metaphysicians and philosophers of mind are inconsistent: (1) there is no systematic overdetermination, and (2) some causal effects are also determined by their metaphysical grounds. Call this "The Problem of Secondary Effects." After introducing the problem and noting philosophical theories that face it, the paper offers further clarification by considering three potential strategies for solving it. All fail. An approach that sacrifices 'secondary effects' is briefly sketched as a solution.